Stochastic description for open quantum systems - Calzetta, Esteban Adolfo (2003)
A linear quantum Brownian motion model with a general spectral density function is considered. In the framework of the influence functional formalism, a Langevin equation can be introduced to describe the system's fully quantum properties even beyond the semiclassical regime. In particular, we show that the reduced Wigner function for the system can be formally written as a double average over both the initial conditions and the stochastic source of the Langevin equation. This is exploited to provide a derivation of the master equation for the reduced density matrix alternative to those existing in the literature. Furthermore, we prove that all the correlation functions obtained in the context of the stochastic description associated to the Langevin equation actually correspond to quantum correlation functions for system observables. In doing so, we also compute the closed time path generating functional of the open system. © 2002 Elsevier Science B.V. All rights reserved.